2008
DOI: 10.1111/j.1365-2141.2008.07072.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of suppressors of cytokine signalling in Philadelphia‐negative chronic myeloproliferative disorders

Abstract: SummaryPh-negative chronic myeloproliferative disorders (CMPD) are characterized by constitutive Janus kinase-signal transducer and activator of transcription (JAK-STAT) activation. SOCS3, SOCS1 and PTPN6 (SHP1) are negative regulators of the JAK-STAT pathway. We investigated epigenetic and genetic inactivation of SOCS3, SOCS1 and PTPN6 in 112 CMPD and 20 acute myeloid leukaemia (AML) post-CMPD. SOCS3 methylation occurred at high frequency in both CMPD (46/112; 41AE1%) and AML post-CMPD (10/17; 58AE8%) and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 41 publications
2
48
2
2
Order By: Relevance
“…For example, mechanisms that were reported to interfere with SOCS function are methylation (Yoshikawa et al, 2001;Galm et al, 2003;Ekmekci et al, 2004), mutations (Melzner et al, 2005) and deletions (Melzner et al, 2006) of SOCS genes. It is important that epigenetic silencing of SOCS3 and SOCS1 was recently reported in B40% of patients with Ph-negative chronic myeloid disorders (Capello et al, 2008;Teofili et al, 2008). The mechanism of mutant Jak2 regulation that we report strongly suggests that the regulation and potential mutation of SOCS proteins could be important clinical parameters in patients carrying constitutively active Jak2 proteins.…”
Section: Regulation Of Mutant Jak2 By Socs Proteinssupporting
confidence: 57%
“…For example, mechanisms that were reported to interfere with SOCS function are methylation (Yoshikawa et al, 2001;Galm et al, 2003;Ekmekci et al, 2004), mutations (Melzner et al, 2005) and deletions (Melzner et al, 2006) of SOCS genes. It is important that epigenetic silencing of SOCS3 and SOCS1 was recently reported in B40% of patients with Ph-negative chronic myeloid disorders (Capello et al, 2008;Teofili et al, 2008). The mechanism of mutant Jak2 regulation that we report strongly suggests that the regulation and potential mutation of SOCS proteins could be important clinical parameters in patients carrying constitutively active Jak2 proteins.…”
Section: Regulation Of Mutant Jak2 By Socs Proteinssupporting
confidence: 57%
“…However, our data suggest SHP1 was methylated in 51/118 (43.2%) MPN patients. The frequency of methylation in our study is significantly higher than the results from Capello et al (2008) As reported that MSP may induce the false positive result, bisulfiteconverted DNA from K562 and 10 MPN patients with hypermethylation of SHP1 were performed sequencing. Our data suggest that sequence of CpG island in K562 and 10 MPN patients showed the expected nucleotide change.…”
Section: 2219 Methylated Alteration Of Shp1 and Mutation Of Jak2 Tyrcontrasting
confidence: 49%
“…Thus, our results are reliable. Although Capello et al reported hypermethylation of SOCS3 occurred in 46 of 112 (41.1%) MPN patients, Fourouclas and his colleage demonstrated hypermethylation of the SOCS3 promoter was only identified in 16 of 50 (32%) patients with IMF but not in patients with ET and PV (Capello et al, 2008). We speculate that the reason for this discrepancy may be the different selection of CpG island prediction methods, different PCR specificity and sensitivity, or a different patient selection criteria.…”
Section: 2219 Methylated Alteration Of Shp1 and Mutation Of Jak2 Tyrmentioning
confidence: 67%
See 2 more Smart Citations